Real space crystallography of a complex metallic alloy: high‐angle annular dark‐field scanning transmission electron microscopy of o‐Al4(Cr, Fe). (1st June 2014) - Gaspari, Roberto; Erni, Rolf; Arroyo, Yadira; Parlinska‐Wojtan, Magdalena; Dshemuchadse, Julia; Pignedoli, Carlo A.; Passerone, Daniele; Schmutz, Patrik; Beni, Alessandra
<x xml:space="preserve">Abstract</x> High‐angle annular dark‐field scanning transmission electron microscopy (HAADF STEM) has been performed along the low‐index zone axes of the o‐Al4(Cr, Fe) complex metallic alloy to obtain a real‐space representation of the crystal structure and to elucidate the material's inherent structural disorder. By comparing experiments with multislice STEM simulations, the model previously suggested by X‐ray diffraction is further refined to provide a new set of positions and occupancies for the transition metal atoms. Pmnb is suggested as the new space group for the o‐Al4(Cr, Fe) phase. A nonperiodic layer‐type modulation, averaged out in bulk diffraction methods, is detected, corroborating the need for complementing bulk diffraction analysis with real‐space imaging to derive the true crystal structure of Al4(Cr, Fe).